Дослідження динаміки формування оксидних плівок на сплаві TI6AL4V у електролітах на основі етиленгліколю - Токайчук, Т. М.; Сьомкіна, Олена Володимирівна; Смірнова, Ольга Леонідівна; Панчева, Ганна Михайлівна; Пилипенко, Олексій Іванович (Видавничий дім "Гельветика", 2020)
Наведені результати дослідження утворення оксидних плівок на сплаві Ti6Al4V у електролітах, що складаються з етиленгліколю, води (5 об. %) і NH₄F. Показано, що за с(NH₄F) = 0,5–2,0 г∙л⁻¹ формувальні залежності, що відображають динаміку утворення оксидних плівок на металі при електрохімічному окисленні, є лінійними залежностями напруги на комірці від часу електролізу. Отримані дані вказують на те, що анодне окислення сплаву за цих умов приводить до утворення оксидних плівок діелектричного типу, для яких максимальна товщина визначається величиною напруги. Забарвлення отриманих плівок не залишається постійним і не відповідає кольору плівок, отриманих у разі оксидування сплаву в електролітах, що не містять іонів-активаторів. Кут нахилу формувальних залежностей збільшується зі зростанням густини анодного струму, що узгоджується з пропорційним збільшенням швидкості окислення металу під час підвищення заданого значення густини струму jₐ. У електролітах, що містять NH₄F у кількості 2,5 г∙л⁻¹ і вище, вид формувальних залежностей визначається jₐ. За високих jₐ лінійний хід залежностей вказує на те, що швидкість утворення плівки перевищує швидкість її хімічного розчинення. За jₐ = 1–2 А∙дм⁻² залежності втрачають лінійний характер, і відбувається утворення пористих оксидних плівок. Отримані дані дозволяють зробити висновок про можливість формування плівок бар’єрного та пористого типів шляхом зміни параметрів електролізу при електрохімічному окисленні сплаву Ti6Al4V у розчинах на основі етиленгліколю. Вони є передумовою для розробки технологічних основ отримання оксидних плівок з функціональними властивостями з можливістю використання як біоінертних і біосумісних покриттів основи для отримання каталізаторів, корозійностійких покриттів.

The data obtained during the studies of the peculiarities of the formation of oxide films on the Ti6Al4V alloy in the electrolytes consisting of ethylene glycol, a small quantity of water (5 vol. %) and ammonia fluoride have been given. It was shown that the forming dependences that reflect the formation dynamics of oxide films on the alloy during the electrochemical oxidation in the electrolytes with ammonia fluorides concentrations varying in the range of 0.5 to 2 g∙l⁻¹ represent a linear dependence of the cell voltage on the electrolysis time. The obtained data are indicative of that the anode oxidation in the alloys under these conditions results in the formation of the oxide films of a dielectric type and in this case a maximum thickness is defined by the voltage value. The color of obtained films is not permanent and it is not corresponding to the color of the films obtained during the oxidation of alloy in the electrolytes that contain no activating ions. The slope angle of forming dependences is increased with an increase in the anode current density and it agrees with a proportional increase in the metal oxidation rate with an increase in the preset value of jₐ. For the electrolytes with the ammonia fluoride concentration of 2.5 g∙l⁻¹ and higher the type of forming dependences is defined by the used current density. At high current densities, a linear behavior of the dependences is indicative of that the film formation rate exceeds that of its chemical dissolution. At the current densities of 1 to 2 А∙dm⁻² the dependences lose their linear behavior and porous oxide films are formed. The obtained data allow us to draw a conclusion on the possibility of the formation of the films of barrier and porous types by way of a change in electrolysis parameters during the electrochemical oxidation of the Ti6Al4V alloy in ethylene glycol-based solutions. These serve as a prerequisite for the development of technological bases for the formation of oxide films with the functional properties that would allow them to be used as bioinert and biocompatible coatings and serve as a base for the formation of photocatalysts and corrosion-resistant coatings.
Study of the dynamics of formation oxide films on TI6AL4V alloy in ethylene glycol based electrolytes
Keywords: анодна поляризація; хімічні реакції; електрохімічне осадження; поляризаційна залежність; діоксид титану; anode polarization; electrochemical oxidation; oxide film; forming dependence